Effect of Cooking Techniques on the in vitro Protein Digestibility, Fatty Acid Profile, and Oxidative Status of Mealworms (Tenebrio molitor) - Mancini, Simone; Mattioli, Simona; Paolucci, Simone; Fratini, Filippo; Dal Bosco, Alessandro; Tuccinardi, Tiziano; Paci, Gisella (Frontiers in Veterinary Science, 2021)
Tenebrio molitor (T. molitor) (mealworm) larvae are one of the most promising insects for feed–food purposes. Mealworms are rich in several macro and micro nutritional elements and can be practically reared on side stream substrates. In this study, the effects of seven different cooking techniques were tested on the nutritional value of mealworms focusing the attention on protein digestibility, fatty acid (FA) profile, and oxidative status. Uncooked larvae (UC) were used as control and compared to two combinations of temperature/time in oven cooking (70°C for 30 min, OC70-30, 150°C for 10 min, OC150-10), two methods of frying (mealworms fried in sunflower oil as deep fry, DF, or pan fry, PF), microwaving (MW), boiling (in plastic bag under vacuum, BO), and steaming (ST). Proximate composition, in vitro digestibility (gastric and duodenal), FA profile, and oxidative status (tocopherol and tocotrienol, carbonyl, and lipid oxidation) were then tested. Cooking technique affected all the tested parameters. As expected, cooking affected proximate composition in relation to the method applied (dry matter increased after oven cooking and frying; lipids increased by frying). In vitro digestion revealed the highest value for the OC70-30 method, followed by UC and ST. Deep frying revealed the worst digestibility percentage. FA profile was deeply affected by the cooking technique, with general decrease in SFA and MUFA. The highest modifications in FA profile were revealed in ST larvae with an increased percentage of linoleic acid linked to the lowering of SFA and MUFA contents. Furthermore, deep frying larvae in sunflower oil increased the relative abundance of PUFAs. Tocols values were higher in DF and MW groups than PF (about 6-fold more) and all other groups (7-fold more). Carbonyls increased with oven cooking (OC150-10 and OC70-30), whereas the values were lower with frying and similar to ST and UC. Lipid oxidation was highest as well in OC150-10 but similar to frying methods (DF and PF). Based on the obtained results, it can be concluded that mealworm larvae surely meet human nutritional requirements, but the cooking method must be carefully chosen to maintain a high nutritional value.